Pengaruh Citra Merek, Brand Trust, Dan Electronic Word Of Mouth Terhadap Keputusan Pembelian Lip Produk Wardah (Wardah Moist Dew Tint) Di E-Commerce - Putri, Alya Kurnia; Nursal, M. Fadhli; Sumantyo, Franciscus Dwikotjo Sri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Even though it is a well-known brand, some consumers still have doubts when purchasing Wardah products through e-commerce platforms. This study aims to determine the influence of brand image, brand trust, and electronic word of mouth (eWOM) on the purchase decision of Wardah Moist Dew Tint lip products through e-commerce platforms. The research method used is quantitative, with questionnaires distributed to 98 respondents in the Bekasi area who have purchased the product. Data were analyzed using SPSS software. The results show that all three independent variables have a positive and significant effect on purchase decisions, both partially and simultaneously, with eWOM being the most dominant factor. These findings highlight the importance of managing digital reviews, brand image, and brand trust in online cosmetic marketing strategies.